2020
DOI: 10.1097/hjh.0000000000002435
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnoea syndrome and left ventricular hypertrophy: a meta-analysis of echocardiographic studies

Abstract: Aim: We investigated the association between obstructive sleep apnoea (OSA) and subclinical cardiac organ damage through a meta-analysis of echocardiographic studies that provided data on left ventricular hypertrophy (LVH), assessed as a categorical or continuous variable. Design: The PubMed, OVID-MEDLINE, and Cochrane library databases were systematically analyzed to search English-language articles published from 1 January 2000 to 15 August 2019. Stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 58 publications
1
19
0
1
Order By: Relevance
“…Night-time blood pressure is a strong predictor of cardiovascular diseases (CVD) [56,57]. The severity of OSA has been associated with the risk of left ventricular hypertrophy [58]. Consequently, management of blood pressure is important to prevent CVD in patients with OSA.…”
Section: Discussionmentioning
confidence: 99%
“…Night-time blood pressure is a strong predictor of cardiovascular diseases (CVD) [56,57]. The severity of OSA has been associated with the risk of left ventricular hypertrophy [58]. Consequently, management of blood pressure is important to prevent CVD in patients with OSA.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to controls, the OSA group exhibited an increased risk of both concentric (OR = 1.62, CI: 1.27-2.07) and eccentric (OR = 1.34, CI: 1.07-1.67) LVH. Finally, a large meta-analysis of our group (5550 patients with OSA and 2329 non-OSA controls from 39 studies) showed that the likelihood of developing LVH increases with the severity of the syndrome with a continuous relationship [35] (Table 1).…”
Section: Left Ventricular Hypertrophy (Lvh)mentioning
confidence: 92%
“…During the past two decades, numerous experimental and clinical reports have considered IH to be the main contributor to OSA-associated cardiovascular complications and mortality [ 4 6 ]. Systematic reviews and meta-analyses have reported that OSA patients exhibit increased left ventricular (LV) hypertrophy, dilation and subclinical markers of LV diastolic dysfunction in accordance with the severity of IH [ 7 9 ]. OSA-associated cardiac remodelling results in impaired LV systolic function ( i.e.…”
Section: Introductionmentioning
confidence: 99%